HEAD OF STATE IN ROMANIA. DESIGNATION. DURATION OF MANDATE - Oana ŞARAMET (Bulletin of the Transilvania University of Braşov Series VII: Social Sciences • Law • Vol. 7 (56) No. 2 - 2014, 2014)
While the existence of some political-judicial institutions, such as the Parliament, has been contested overtime, in different social-political and historical times, and the people or the nation have always reclaimed the existence of a leader and the state’s power organization did not cause it to disappear but to transform that leader into a true head of state.